DISTANCE ENGLISH EDUCATION PROGRAM EVALUATION AT UNIVERSITAS TERBUKA - Nugraha, Benny (2012)
The issues of quality in distance education and the lack of studies in distance program evaluation inspired the researcher to conduct a formative evaluation of the English Education Program (EEP) at Universitas Terbuka (UT). Conducted in a period from April to June 2012, the evaluation focused on the assessment of EEP performance in meeting the standards. Adapting the Discrepancy Evaluation Model from Provus (1969) with four evaluation stages, it assessed EEP performances in developing and implementing its program components including student, staff, objectives, content, delivery method, learning assessment, support systems, and facilities. Document analysis was conducted to describe EEP and to compare it with the standards. Next, cross-sectional surveys were administered to EEP students and administrators Returned responses from fifty-six students and sixteen administrators were used as the primary data for quantitative data analysis. The analysis revealed that the program implementation performance was not congruent with the standards. Discrepancies in EEP components were found in such components as support systems, learning assessment, and staff. This finding was supported by the results of content analysis of the open-ended question responses confirming that tutorial support should be provided for every course. The evaluation concluded that (1) EEP performances were not congruent with the standards, and (2) Discrepancies were found in EEP design and implementation of support systems, staff, and learning assessment. It suggested that improvement attempts be conducted on EEP components/subcomponents such as tutorial, staff, learning assessment, information and communication services, library services, and academic counseling